MODERNIZATION OF ISLAMIC RELIGIOUS EDUCATION IN MADRASAH: BALANCING RELIGIOUS KNOWLEDGE AND SCIENCE - Muna Hatija; Akhsanul In’am; Khozin Khozin; Faridi Faridi (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aimed to analyze the strategy of modernizing Islamic religious education in madrasas to integrate religious knowledge and science, identify its implementation challenges, and examine its impact on students. Using a qualitative approach with a case study at MAN Palopo, the study involved principals, teachers, education personnel, madrasa committees, and grade XI IPA students. The results indicated that modernization was achieved by integrating Islamic and science curricula, project-based learning (PjBL) methods, and contextual approaches. The main challenges included limited interdisciplinary human resources, minimal technological infrastructure, educators and community resistance, and a lack of supporting regulations. This modernization positively impacted improving students’ scientific understanding, critical thinking, academic achievement, and religious awareness. The study recommended interdisciplinary training for teachers, technological infrastructure development, and flexibility of integration-based curricula. The implications of this research highlight that the modernization of Islamic religious education can serve as a model for other madrasas, encouraging policymakers to design more supportive regulations and enabling schools to balance faith-based values with scientific literacy in preparing students for global challenges.